2024
DOI: 10.7150/ijbs.83306
|View full text |Cite
|
Sign up to set email alerts
|

SIRT5-related lysine demalonylation of GSTP1 contributes to cardiomyocyte pyroptosis suppression in diabetic cardiomyopathy

Can Wei,
Meixin Shi,
Shiyun Dong
et al.

Abstract: Sirtuin 5 (SIRT5), localized in the mitochondria, has been identified as a protein desuccinylase and demalonylase in the mitochondria since the depletion of SIRT5 boosted the global succinylation and malonylation of mitochondrial proteins. We investigated the role of SIRT5 in diabetic cardiomyopathy (DCM) and identified the mechanism regarding lysine demalonylation in this process. Wild-type and SIRT5 knockout mice were induced with DCM, and primary cardiomyocytes and cardiac fibroblasts extracted from wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, AEC in the lung are active progenitors and secretory cells containing approximately 50% of lung mitochondrial mass (Hong et al 2023;Lee et al 2023), so it is reasonable to speculate that AEC senescence in IPF may be due to the occurrence of mitochondrial hyperKsucc. SIRT5, a mitochondrial sirtuin with very weak deacetylase activity, is a potent desuccinylase, the catalytic reaction involves the removal of a succinyl group from the lysine side chain of protein substrates (Wei et al 2024). SIRT5 as a global regulator of Ksucc in mitochondria has been reported that sirtuins depletion is related to the progression of pulmonary fibrosis, and increasing expression of sirtuins protein plays a protective role in pulmonary fibrosis (Shaikh et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, AEC in the lung are active progenitors and secretory cells containing approximately 50% of lung mitochondrial mass (Hong et al 2023;Lee et al 2023), so it is reasonable to speculate that AEC senescence in IPF may be due to the occurrence of mitochondrial hyperKsucc. SIRT5, a mitochondrial sirtuin with very weak deacetylase activity, is a potent desuccinylase, the catalytic reaction involves the removal of a succinyl group from the lysine side chain of protein substrates (Wei et al 2024). SIRT5 as a global regulator of Ksucc in mitochondria has been reported that sirtuins depletion is related to the progression of pulmonary fibrosis, and increasing expression of sirtuins protein plays a protective role in pulmonary fibrosis (Shaikh et al 2019).…”
Section: Introductionmentioning
confidence: 99%